Magnetization Transfer Imaging Predicts Porcine Kidney Recovery After Revascularization of Renal Artery Stenosis. Issue 2 (February 2021) - Afarideh, Mohsen; Jiang, Kai; Ferguson, Christopher M.; Woollard, John R.; Glockner, James F.; Lerman, Lilach O.
Objectives: Magnetization transfer imaging is a novel noninvasive tool for the detection of kidney fibrosis, but its association with kidney function and hemodynamics is unclear. Renovascular disease (RVD) associated with metabolic derangements elicits renal fibrosis and is often unresponsive to percutaneous transluminal angioplasty (PTRA), but tools to predict therapeutic success are unavailable. We hypothesized that magnetization transfer imaging predicts kidney recovery after PTRA in swine with unilateral RVD. Materials and Methods: Stenotic kidney (STK) and contralateral kidney magnetization transfer ratios (MTRs; M t / M 0 ) were measured at 3.0-T magnetic resonance imaging, at offset frequencies of 600 and 1000 Hz, before and 1 month post-PTRA in 7 RVD pigs. Stenotic kidney MTR was correlated to renal perfusion, renal blood flow (RBF), and glomerular filtration rate (GFR), determined using multidetector computed tomography and with ex vivo renal fibrosis (trichrome staining). Untreated RVD (n = 6) and normal pigs (n = 7) served as controls. Results: Renovascular disease induced hypertension and renal dysfunction. Blood pressure and renal perfusion were unchanged post-PTRA, but GFR and RBF increased. Baseline cortical STK-MTR predicted post-PTRA renal perfusion and RBF, and MTR changes associated inversely with changes in perfusion and normalized GFR. Stenotic kidney MTR at 600 Hz showed closer association with renal parameters, but both frequencies predicted post-PTRA cortical fibrosis. Conclusions: Renal STK-MTR, particularly at 600 Hz offset, is sensitive to hemodynamic changes after PTRA in swine RVD and capable of noninvasively predicting post-PTRA kidney perfusion, RBF, and fibrosis. Therefore, STK-MTR may be a valuable tool to predict renal hemodynamic and functional recovery, as well as residual kidney fibrosis after revascularization in RVD. Abstract : Supplemental digital content is available in the text.